Integration of the Al-Quran Memorization Curriculum with the Formal Curriculum at MTs Pembangunan UIN Jakarta - Silmi Adawiya; Suwendi Suwendi (Electronic Journal of Education, Social Economics and Technology, 2025)
The integration of the Al-Qur'an memorization curriculum with the formal curriculum is an important aspect in realizing the goals of education and the memorization program simultaneously. This study aims to analyze the implementation of the Al-Qur'an memorization class curriculum at MTs Pembangunan UIN Jakarta. This study uses a qualitative approach with a field research type. Data collection techniques used include observation, interviews, and documentation. The results of the study indicate that the Al-Qur'an memorization class curriculum at MTs Pembangunan UIN Jakarta is designed with the main objective of forming the habit of memorizing the Al-Qur'an and understanding it intensively. The Al-Qur'an memorization material includes a memorization target of 10 juz within a period of three years. The method used in the learning process is the talaqqi method, while memorization evaluation is carried out through sima'an, namely listening to the memorization of one to five juz in front of the examiner. This study provides a significant contribution to understanding and developing the implementation of the Al-Qur'an memorization class integrated into the formal education curriculum. By describing the model of integration between the tahfiz curriculum and the national curriculum implemented in schools, this study reveals how this integration can increase the effectiveness of learning to memorize the Qur'an systematically and sustainably.